Vesicovaginal fistula following pelvic surgery: Our experiences and recommendations for diagnosis and prompt referral. (21st February 2020) - Thayalan, Krishanthy; Parghi, Sneha; Krause, Hannah; Goh, Judith
Abstract : Background: Vesicovaginal fistula (VVF) is an uncommon but known complication of pelvic surgery. Post‐operative urine leakage should generate a high index of clinical suspicion for early diagnosis of VVF. Aims: This study aims to identify areas for improvement and provide recommendations for timely and accurate diagnosis of VVF to minimise patient morbidity. Materials and Methods: A retrospective observational study of all patients who underwent VVF repairs unrelated to malignancies in a ten‐year period at two primary referral centres in Brisbane was performed to review the aetiology, performance of investigative tests and management of these cases. Results: A total of 56 patients were studied with the identification of significant delays to diagnosis and referral, the performance of multiple unnecessary tests and low rates of primary surgeon referral. Conclusions: Early recognition of VVF and assessment by outpatient methylene blue dye test can provide quick same‐day diagnosis and minimise patient suffering. We hope this will alert gynaecologists and provide guidelines for diagnosis and improved management to allow for prompt referral and repair of genitourinary fistula.